2021
DOI: 10.1590/1982-0275202138e190168
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact on family caregivers of children and adolescents with sickle cell anemia

Abstract: Sickle cell anemia represents an aversive context, placing the family in a situation of vulnerability. This study investigated the psychological impact of sickle cell anemia on family caregivers of children and adolescents with this disease. A research with a quantitative approach followed by a survey was carried out, with a non-probabilistic sample of 100 caregivers who answered the instruments for measuring family functioning, disease-related stress, coping, anxiety, and depression. Clinical and sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
1
0
3
Order By: Relevance
“…Thus, findings from the current study indicate caregiver resilience and the use of adaptive coping strategies. These results are somewhat consistent with findings from a recent study of coping among caregivers of youth with SCD in Brazil,42 although the study indicated lower proportion scores for caregiver PCE coping compared with the current study. Findings from the current study are also comparable to findings from other chronic illness populations; proportion scores for caregiver PCE and disengagement coping in the current study are similar to RSQ coping proportion scores among caregivers of youth with asthma,22 type 1 diabetes,59 and cancer 55.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, findings from the current study indicate caregiver resilience and the use of adaptive coping strategies. These results are somewhat consistent with findings from a recent study of coping among caregivers of youth with SCD in Brazil,42 although the study indicated lower proportion scores for caregiver PCE coping compared with the current study. Findings from the current study are also comparable to findings from other chronic illness populations; proportion scores for caregiver PCE and disengagement coping in the current study are similar to RSQ coping proportion scores among caregivers of youth with asthma,22 type 1 diabetes,59 and cancer 55.…”
Section: Discussionsupporting
confidence: 92%
“…Proportion scores are used to control for response bias as well as individual differences in base rates of item endorsement; their use has been supported in the coping literature 40,41. The RSQ has been used in SCD39,42 and its factor structure has been supported by confirmatory factor analysis studies in a range of diverse samples 19. The RSQ has also demonstrated acceptable psychometric properties in various disease populations 43,44.…”
Section: Methodsmentioning
confidence: 99%
“…Pesquisa realizada salientou constantes anseios dos familiares cuidadores de crianças com doença falciforme para compreender os diferentes aspectos que permeiam essa enfermidade sobretudo no que se refere ao enfrentamento e tratamento necessários no cotidiano, os quais podem, por sua vez, gerar eventos estressantes como ansiedade e depressão (18) .…”
Section: Discussionunclassified
“…No estudo realizado por Caprini & Motta (2021), apesar da assistência continua ofertada pelo cuidador familiar, e seus medos de situações agravantes, não foi evidenciado predomínios de ansiedade ou depressão, ou seja, os familiares possuem um ajuste emocional e mental estável, o que proporciona estabilidade para desempenhar suas atividades cotidianas. (Garioli, Paula, Enumo, 2019).…”
Section: Autores Objetivo Anounclassified